General Purpose Technologies and local knowledge accumulation — A study on MNC subunits and local innovation centers. Issue 4 (August 2018) - Qiu, Ranfeng; Cantwell, John
Highlights: This research looks into the innovative activities of subunits of large non-U.S firms in the U.S from 1969 to 1995, suggesting that the innovations in the subunits of multinational corporations are closely linked to their specializations in General Purpose Technologies (GPTs). GPTs enable recombining knowledge from different domains on an international scale, and that the specialization of innovations in GPT fields within a subunit is positively associated with the innovative capacity at large, along with the degree of technological diversification of that specific subunit. As firms expand geographically to tap into local innovation centers to develop new growth alternatives, specialization of GPTs in these firms actually facilitates further geographical dispersion of innovative activities across locations. Additional specializations of innovations in GPT fields within the host innovation centers does help in attracting innovation activities of firms from a wider range of industries. Abstract: This research looks into the innovative activities of subunits of large non-U.S firms in the U.S from 1969 to 1995, suggesting that the innovations in the subunits of multinational corporations are closely linked to their specializations in General Purpose Technologies (GPTs). GPTs enable recombining knowledge from different domains on an international scale, and that the specialization of innovations in GPT fields within a subunit is positively associated with the innovative capacity at large, along with the degree of technological diversification of that specific subunit. As firms expand geographically to tap into local innovation centers to develop new growth alternatives, specialization of GPTs in these firms actually facilitates further geographical dispersion of innovative activities across locations. Lastly, additional specializations of innovations in GPT fields within the host innovation centers does help in attracting innovation activities of firms from a wider range of industries.